If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 = 3x + 11 Reorder the terms: 1 + 4x = 3x + 11 Reorder the terms: 1 + 4x = 11 + 3x Solving 1 + 4x = 11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + 4x + -3x = 11 + 3x + -3x Combine like terms: 4x + -3x = 1x 1 + 1x = 11 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + 1x = 11 + 0 1 + 1x = 11 Add '-1' to each side of the equation. 1 + -1 + 1x = 11 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 11 + -1 1x = 11 + -1 Combine like terms: 11 + -1 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| x/3-1/2=1/12 | | 6x+12=3+8x-7 | | 6x+12=3+8x-7 | | 27=-18+9c | | 7x+2=5x-6+8 | | 3(19x+20)=9(7+6x)-1 | | 17x-5=7+15x | | .6w-.4w+.3w=5 | | [k-10]=3 | | 5x+20=6x+8 | | 6(2x-9)+1=6(3x-7)-8(x+2) | | 20=4x+2 | | 2x+3=3x-15 | | 2x+5(2x+1)=7(x-1)-3 | | 2n-10n=40 | | 11x-8-6x=6x-7 | | 1.5x-5=x-4.5 | | 3(7x-8)=4(6x-3) | | 6x+5=-7+2x+20 | | 27=3c+-18+6c | | 7x+20=3x+30 | | 6x+4+15=36 | | 4(6-5x)=3(7-5x) | | [6m]=42 | | 3x+2(x+3)=4(2x-1)-5 | | 6-6x-4=-46+3x-15 | | 4(5x-6)=10x+12x-2x | | 8x+5=4(3x-2)-3 | | 21+1.5h=28-2h | | x^2-3xy+2y^2-y+x=0 | | 11-(2x+5)=-5x+7 | | x/3-1/2=1/2 |